2021
DOI: 10.3389/fmed.2021.591830
|View full text |Cite
|
Sign up to set email alerts
|

D-Limonene Is a Potential Monoterpene to Inhibit PI3K/Akt/IKK-α/NF-κB p65 Signaling Pathway in Coronavirus Disease 2019 Pulmonary Fibrosis

Abstract: At the time of the prevalence of coronavirus disease 2019 (COVID-19), pulmonary fibrosis (PF) related to COVID-19 has become the main sequela. However, the mechanism of PF related to COVID (COVID-PF) is unknown. This study aimed to explore the key targets in the development of COVID-PF and the mechanism of d-limonene in the COVID-PF treatment. The differentially expressed genes of COVID-PF were downloaded from the GeneCards database, and their pathways were analyzed. d-Limonene was molecularly docked with rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…The inflammation caused by the host immune system during COVID-19 can lead to pathological injuries, including acute respiratory distress syndrome (ARDS) and eventual death. High percentages of Th17 and low percentages of Treg have been reported in COVID-19 patients [ 1 ]. Previous studies have shown that mTORC1 plays a role in inducing Th17 and Th1 differentiation during viral infections, and mTORC2 can enhance Th2 differentiation, while both complexes reduce Treg differentiation [ 11 ].…”
Section: The Mtor Pathway In the Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The inflammation caused by the host immune system during COVID-19 can lead to pathological injuries, including acute respiratory distress syndrome (ARDS) and eventual death. High percentages of Th17 and low percentages of Treg have been reported in COVID-19 patients [ 1 ]. Previous studies have shown that mTORC1 plays a role in inducing Th17 and Th1 differentiation during viral infections, and mTORC2 can enhance Th2 differentiation, while both complexes reduce Treg differentiation [ 11 ].…”
Section: The Mtor Pathway In the Immune Systemmentioning
confidence: 99%
“…Once the virus enters, the activation of eukaryotic translation initiation factor 4E-binding protein1 (4-E-BP1) and ribosomal protein S6 kinase beta 1 (S6K1) (downstream mTOR compounds) leads to increased synthesis of ribosomes and proteins (including viral proteins) [ 9 ]. SARS-CoV-2 infection can lead to hyperactivation of mTOR in vitro, and since the unregulated activation of the mTOR pathway plays a decisive role in COVID-19-induced pathogenesis, inhibiting this pathway can prevent the progression of infection [ 1 ]. Thus, drug inhibitors of the mTOR or microRNAs that interact with 3-UTR of mTOR could be a proper candidate for treating COVID-19 patients [ 9 ].…”
Section: Sars-cov-2 and Mtor Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to thrombosis, one of the outcomes of COVID-19 is pulmonary fibrosis. Interestingly, the PI3K/Akt pathway was identified as a therapeutic target for COVID-19 associated pulmonary fibrosis and, in a bleomycin-induced lung fibrosis rat model, targeting the pathway using D -Limonene was protective against fibrosis [47] .…”
Section: Thrombosismentioning
confidence: 99%
“…NF-κB p65 is usually bound to the cytoplasm in an inactive form with the IKB inhibitory factor. When bacteria, viruses, or cytokines stimulate the cells, IKB and NF-κB p65 are degraded by activated IKK; thus, the latter is activated in the nucleus to perform its functions [ 15 ]. One of the most important antioxidant signaling pathways in the body is the NLRP3 signaling pathway [ 16 ].…”
Section: Introductionmentioning
confidence: 99%